Nasionalisme Banser NU (Nasionalisme dalam perspektif Banser NU Magelang) - Moh. Fatkhan (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2018)
This paper seeks to see nationalism among Banser in Magelang District. In the historical record, Multiple Ansor Movement of the Nahdlatul Ulama (NU) nationalism is undoubtedly, among other things how Banser secures Pancasila and actively participates with society and government in maintaining the unity and defending NKRI. History has proven post-G 30 S / PKI eruption, GP. Ansor and Banser have been instrumental in the G.30.S / PKI crackdown. Ansor Multipurpose Group is the core force of Ansor Youth Movement as a cadre of movers, caretakers and security of social programs of Ansor Youth Movement. The aforementioned cadres are members of the Ansor Youth Movement that have qualifications: Discipline and high dedication, strong physical and mental resilience, mental and religious as the bastion of the ulama and can realize the ideals of Ansor Youth Movement and the common good. Based on the results of this study found that the attitude of Banser nationalism in the willingness to sacrifice can be realized by helping friends and others with sincerity without expecting any reward, able to prioritize the public interest rather than personal interests, and willing to defend the nation and state. In the context of Diklatsar Banser, there is a great need for awareness to raise citizens who are dedicated to the nation and state.[Tulisan ini berupaya melihat nasionalisme di kalangan Banser di Kabupaten Magelang. Dalam catatan sejarah, nasionalisme Barisan Ansor Serbaguna (Banser) Nahdlatul Ulama (NU) sudah tidak diragukan lagi, di antaranya saat bagaimana Banser mengamankan Pancasila dan berpartisipasi aktif bersama masyarakat serta pemerintah dalam menjaga keutuhan dan mempertahankan NKRI. Sejarah telah membuktikan pasca meletusnya G 30 S/PKI, GP. Ansor dan Banser telah berjasa dalam penumpasan G.30.S/PKI. Barisan Ansor Serbaguna adalah tenaga inti Gerakan Pemuda Ansor sebagai kader penggerak, pengemban dan pengaman program-program sosial kemasyarakatan Gerakan Pemuda Ansor. Kader dimaksud adalah anggota Gerakan Pemuda Ansor yang memiliki kwalifikasi: Disiplin dan dedikasi yang tinggi, ketahanan fisik dan mental yang tangguh, penuh daya juang dan religius sebagai benteng ulama dan dapat mewujudkan Gita-cita Gerakan Pemuda Ansor dan kemaslahatan umum. Berdasarkan hasil penelitian ini didapat bahwa sikap nasionalisme Banser dalam aspek rela berkorban dapat diwujudkan dengan cara membantu teman maupun orang lain dengan ikhlas tanpa mengharapkan imbalan apapun, mampu mendahulukan kepentingan umum daripada kepentingan pribadi, dan bersedia membela bangsa dan negara. Di dalam konteks Diklatsar Banser, amat dibutuhkan kesadaran untuk membangkitkan warga negara yang penuh dedikasi terhadap bangsa dan negara.]